Emissive brightening in molecular graphene nanoribbons by twilight states - Sturdza, BK; Kong, F; Yao, X; Niu, W; Feng, X; Riede, M; Bogani, L; Nicholas, R (Springer Nature, 2024)
Carbon nanomaterials are expected to be bright and efficient emitters, but structural disorder, intermolecular interactions and the intrinsic presence of dark states suppress their photoluminescence. Here, we study synthetically-made graphene nanoribbons with atomically precise edges and which are designed to suppress intermolecular interactions to demonstrate strong photoluminescence in both solutions and thin films. The resulting high spectral resolution reveals strong vibron-electron coupling from the radial-breathing-like mode of the ribbons. In addition, their cove-edge structure produces inter-valley mixing, which brightens conventionally-dark states to generate hitherto-unrecognised twilight states as predicted by theory. The coupling of these states to the nanoribbon phonon modes affects absorption and emission differently, suggesting a complex interaction with both Herzberg–Teller and Franck– Condon coupling present. Detailed understanding of the fundamental electronic processes governing the optical response will help the tailored chemical design of nanocarbon optical devices, via gap tuning and side-chain functionalisation.